PROSEDUR PEMUNGUTAN PBJT JASA PERHOTELAN TERHADAP PAJAK DAERAH DI BADAN PENGELOLAAN PAJAK DAN RETRIBUSI DAERAH KOTA BANJARBARU - Anne Agneta Tampi; Sadikin, Ali; Rahmini, Noor (Universitas Lambung Mangkurat, 2025)
This study examines the procedures for collecting Certain Goods and Services Tax (PBJT) on Hotel Services in Banjarbaru City and identifies the obstacles faced by the Regional Tax and Retribution Management Agency (BPPRD). A descriptive qualitative method was used, collecting data through field observations, structured interviews with BPPRD officials and taxpayers, and documentation. The results indicate that although the procedures for data collection, registration, updating, payment, reporting, auditing, and collection are in accordance with regulations, their effectiveness is hampered by outdated data, fluctuations in taxpayer compliance, and limited human resources and technology. Recommendations include strengthening the integrated information system, human resource training, and a taxpayer compliance incentive program.